Isolation, characterization of Vibrio and Pseudomonas spp from infected fresh water ornamental fishes and evaluation of potential agents for its control - Marimuthu, Prabhu Narayanan; Periyannan, Rajasekar; Girijakumari, Nisha Rajagopalan; Ramar, Manikandan (Research in Biotechnology, 2012)
The present work aims at comparing the antibacterial effect of probiotics, plant extracts of Vitex negundo and Clitoria ternatae and antibiotics against the disease causing bacteria isolated from infected ornamental fishes. The molecular characterization of isolated pathogens was performed by randomly amplified polymorphic DNA (RAPD) technique. The antibacterial effects of probiotic and plant extracts were analyzed by well diffusion method and antibiotic disc was performed by disc diffusion method. Isolated probiotics such as Bacillus sp. showed maximum antibacterial activity of 18 mm and 16 mm zone against VibrioÃ‚Â sp (V2) and Pseudomonas sp (Ps1) respectively. Leaf extract of Vitex negundo displayed zone of inhibition of 20 mm on Pseudomonas sp (Ps3) and 16 mm on Vibrio sp (V1). Among the antibiotics,Ã‚Â chloramphenicol and ampicillin showed maximum inhibitory activity against Vibrio sp (V3) (25mm) and Pseudomonas sp (Ps2) (25mm) respectively. Even though, antibiotics showed higher inhibitory activityÃ‚Â than the isolated Bacillus bacteria and plant extract (V. negundo and C. ternatae). This study concluded that the use of probiotics as an alternative strategy to the use of antibiotics because of its effectiveÃ‚Â antibacterial activity and growing concern in violence of disinfectants and antibacterial agents.